Surfing the South The Search for Waves and the People Who Ride Them. - Estes, Steve (University of North Carolina Press, 2022)
"When most Americans think of surfing, they often envision waves off the coasts of California, Hawai'i, or even New Jersey. What few know is that the South has its own surf culture. To fully explore this unsung surfing world, Steve Estes undertook a journey that stretched more than 2,300 miles, traveling from the coast of Texas to Ocean City, Maryland. Along the way he interviewed and surfed alongside dozens of people-wealthy and poor, men and women, Black and white-all of whom opened up about their lives, how they saw themselves, and what the sport means to them. They also talked about race, class, the environment, and how surfing has shaped their identities"--